From laboratory to clinic: a precise treatment strategy of mesenchymal stem cells-derived exosomes pretreated by simulating disease microenvironment - Ye, Hailian; He, Qi; Qi, Fang; Xu, Guangchao; Qahar, Mulan; Deng, Chenliang; Wei, Zairong (Frontiers in Immunology, 2025)
Mesenchymal Stem Cells (MSCs) and their secreted extracellular vesicles (EVs), particularly exosomes (Exos), have garnered significant attention for their potential in tissue repair, fibrosis, and tumor therapy. However, the therapeutic efficacy of mesenchymal stem cell-derived exosomes (MSC-Exos) is notably influenced by the disease-specific microenvironment. This review examines the mechanisms of action of MSCs and MSC-Exos in various diseases and analyzes the impact of inflammatory preconditioning on the functions and paracrine signaling of MSCs. We propose a personalized MSC preconditioning strategy based on the characteristics of the disease microenvironment to enhance the precision and efficacy of MSC-Exos therapy. Additionally, we discuss the limitations of traditional preconditioning strategies and introduce novel approaches for MSC preconditioning by simulating the disease microenvironment, such as using tissue homogenates and EVs derived from diseased tissues. These methods more accurately reflect the spatiotemporal features of the disease microenvironment, thereby improving the therapeutic potential of MSC-Exos. Finally, we explore the application of engineered exosomes loaded with key miRNAs targeting disease treatment, offering new insights for precision medicine.